A study of some cultural characteristics and blood serum antibody titres of enterococci isolated from the mouth and faeces - Slabbert, J.C.G. (My University, 1975)
Crevicular epithelium presents no effective barrier to the biologically active constituents of plaque. Moreover, it seems that the production of circulating antibodies, the development of a state of delayed hypersensitivity and the development of immunological tolerance all play a part in the pathogenesis of periodontal disease. An investigation was undertaken to study the cultural characteristics of enterococci isolated from the mouth and gut of a group of students, and to determinethe serum antibody titres to these organisms. Enterococci were isolated from faeces and the gingival crevice of 9 male dental students. Blood was obtained from each subject and allowed to clot. The serum was removed and stored at -20°C until required. Blood serum antibody titres to the bacteria were obtained by the indirect fluorescent antibody technique.
A Dissertation submitted to the Faculty of Dentistry of the University of the Witwatersrand, Johannesburg, (in partial fulfilment of the requirements) for the degree of Master of Dentistry Johannesburg June 1975
Keywords: Serum; Feces; Mouth; Gingival Crevicular Fluid; Epithelium